(3GdeNJGQ aj cTa GdCSQGQs - (3CHhHcQ YHO GdQMje GdOeTbj GdLhHQjs
(3ChdgG (B:s
(3HYO GdHSedI GdMeO ddg Gdedc GdGYXe CeG HYO MeO Gddg de GWGdYJ cJH GdMceGA hGdSGOI GdeJbOejf ef GdYdeGA QCjJ eG bO hVYhg ef GdYdhe hbQCJ eG hbY dj ef GdcJH s
(3BNQgG (B:s
(3hGYde Cfj eG QSJ cd af hGWdYJ Ydi cd af hYdi cd UfGYI ef hajbgG hLdjgG hde GJQc TjFkG eeG hbaJ Ydjg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3HQdjf JhHfLjf s
Keywords: (3GdcjejGA h GdWHjYjGJs